KOMUNIKASI NIKLAS LUHMANN DALAM MEMBANGUN KERUKUNAN ANTAR UMAT BERAGAMA DI WILAYAH PERKOTAAN - Martha Suhardiyah (Indonesian Journal of Islamic Communication, 2020)
Religious plurality in the era of globalization is a necessity in the midst of cultural heterogeneity, religious expression and religion itself. Religious plurality has a very large potential and role in the process of integrating the development of the Indonesian nation in the future. However, on the other hand, religious plurality contains the potential for conflict and disintegration of the nation, because the dominance of the absolute truth claims of each religion so that emotions become the basis of interaction and communication. Therefore, communication becomes a pillar of religious harmony. To achieve religious harmony, this research uses a qualitative-descriptive method that puts with Niklas Luhmann theory of communication. The results obtained in this study are communication with Lumann view is a social system based on action (activity) using communication tools and attribution as a reduction of the complexity of public trust. This Luhmann style action communication is very important to be applied to the Surabaya urban community in order to create harmony between religious communities. Therefore, the inter-religious community in the urban area of ​​Surabaya builds communication with various models, namely Interpersonal Communication, group communication, Organizational or Institutional communication and cultural communication. This communication model is seen in the daily lives of urban Surabaya communities to foster harmony between religious communities. All of these communication models are supported by mutual respect, mutual acceptance of differences and a culture of mutual cooperation.